Respuesta :
x^(m/n)=[tex] \sqrt[n]{x^m} [/tex]
2^(5/2)=[tex] \sqrt[2]{x^5} [/tex]
2^(3/2)=[tex] \sqrt[2]{x^3} [/tex]
so
2^(5/2)-2^(3/2)=
[tex] \sqrt{2^5} - \sqrt{2^3} [/tex]=
[tex] 4\sqrt{2} - 2\sqrt{2} [/tex]=
[tex] 2\sqrt{2} [/tex]
2^(5/2)=[tex] \sqrt[2]{x^5} [/tex]
2^(3/2)=[tex] \sqrt[2]{x^3} [/tex]
so
2^(5/2)-2^(3/2)=
[tex] \sqrt{2^5} - \sqrt{2^3} [/tex]=
[tex] 4\sqrt{2} - 2\sqrt{2} [/tex]=
[tex] 2\sqrt{2} [/tex]
Answer:
2^(5/2)-2^(3/2)=
\sqrt{2^5} - \sqrt{2^3} =
4\sqrt{2} - 2\sqrt{2} =
2\sqrt{2}
Step-by-step explanation:
x^(m/n)= \sqrt[n]{x^m}
2^(5/2)= \sqrt[2]{x^5}
2^(3/2)= \sqrt[2]{x^3}